Korelasi Kearifan Lokal dengan Kepercayaan Lokal terhadap Tolak Bala di Paluta - Pratama, Aji; Wirman, Wirman; Ryandi, Ryandi (Lembaga Yasin AlSys, 2023)
This research is entitled Correlation of Local Wisdom with Local Trust in Rejecting Reinforcements in Paluta. The problem that arises in this research is How does local wisdom and local trust affect the rejection of reinforcements in Siancimun Village? To what extent does local wisdom play a role in local beliefs and what is the relationship between local wisdom and local beliefs towards Rejecting Bala. Based on the background of the problem above, the author is interested in studying more deeply about repulsion of reinforcements, by comparing two differences, namely, Local Wisdom and Local Beliefs. In this research, the researcher used this type of research, namely field research which is qualitative in nature. The research method used by researchers is a phenomenological approach. In this case, the author also divides it into two data sources, namely primary data and secondary data. The forms of research data are interviews, observation and documentation. The results of this research show that local wisdom is a concept that refers to knowledge, traditions, values and practices that have existed and developed in a particular society for many years. Local wisdom is often related to traditional knowledge, wisdom in adapting to the local natural environment, and ways of life that have been passed down from generation to generation. Meanwhile, local belief is a local belief system which is a belief system or spiritual belief, religion or faith that develops in a particular community or area. Rejecting reinforcements in Siancimun Village, Paluta started from the shrinking of the springs, therefore the ritual of rejecting reinforcements was carried out. This ritual is used to ward off evil in order to avoid the disaster that befell Siancimun Village. Then there is the ritual of rejecting reinforcements in Siancimun Village using offerings to commemorate ancestors. Until now, local wisdom and local beliefs regarding repelling reinforcements are still carried out by the people of Siancimun Village, Paluta.